A new method for determining gossypol in cottonseed oil by FTIR spectroscopy - Mirghani, M. E. S.; Che Man, Y. B. (Wiley, 2003)
A new method was developed to determine the gossypol content in cottonseed oil using FTIR spectroscopy with a NaCl transmission cell. The wavelengths used were selected by spiking clean cottonseed oil to gossypol concentrations of 0–5% and noting the regions of maximal absorbance. Transmittance values from the wavelength regions 3600–2520 and 1900–800 cm−1 and a partial least squares (PLS) method were used to derive FTIR spectroscopic calibration models for crude cottonseed, semirefined cottonseed, and gossypol‐spiked cottonseed oils. The coefficients of determination ( R 2) for the models were computed by comparing the results from the FTIR spectroscopy against those obtained by AOCS method Ba 8‐78. The R 2 were 0.9511, 0.9116, and 0.9363 for crude cottonseed, semirefined cottonseed, and gossypol‐spiked cottonseed oils, respectively. The SE of calibration were 0.042, 0.009, and 0.060, respectively. The calibration models were cross‐validated within the same set of oil samples. The SD of the difference for repeatability and accuracy of the FTIR method were better than those for the chemical method. With its speed ( ca. 2 min) and ease of data manipulation, FTIR spectroscopy is a useful alternative to standard wet chemical methods for rapid and routine determination of gossypol in process and/or quality control for cottonseed oil.